Comprehensive 1-year multilevel study of sports injuries in para athletes: impact of season timing, years of sports experience, impairment and sports type - Evert Verhagen; Erik Witvrouw; Evi Wezenbeek; Fernanda Madaleno; Juliana Ocarino; Renan Resende; Marco Túlio de Mello; Andressa Silva; Larissa Pinheiro; Mauro Heleno Chagas; Dawit Gonçalves (BMJ Open Sport & Exercise Medicine)
Objectives Investigate the associations between season timing, sports experience, impairments and sports type with injuries and time loss among para athletes over a 50-week sports season.Methods Data were collected in 2022 from two Brazilian Paralympic Centres, including para athletes competing in para swimming, para athletics, para powerlifting and para taekwondo. Injuries were recorded weekly using the Oslo Sports Trauma Research Centre Questionnaire on Health Problems Questionnaire. Multilevel logistic regression was used to analyse injury data, and a multilevel zero-inflated negative binomial model was used for time loss. ORs and rate ratios (RRs) were calculated.Results 102 para athletes participated. As the season progressed, we observed fewer gradual-onset (OR=0.97) and sudden-onset injuries (OR=0.97) and less time loss (RR=0.99), but an increase in the odds of substantial gradual-onset injuries (OR=1.04). More years of sports experience were associated with fewer sudden-onset injuries (OR=0.94) and more time loss (RR=1.10). Moreover, para athletes with visual impairments were less likely to experience gradual-onset injuries (OR=0.55) and had less time loss (RR=0.12) than those with physical impairments. Para swimmers experienced fewer gradual (OR=0.65) and sudden-onset (OR=0.52) injuries and had less time loss (RR=0.40) compared with athletes in para athletics, while para powerlifters had fewer sudden-onset injuries than those in para athletics (OR=0.34).Conclusions These findings highlight the importance of considering the investigated factors in injury prevention for para athletes. Careful monitoring throughout the season—especially for para athletes with lower or higher levels of sports experience, those with physical impairments and those competing in para athletics—could yield significant benefits